Livelihood and Conservation in Guinea-Bissau’s National Parks: A Photographic Essay - Abreu, Alexandre (Consilience, 2011)
Guinea-Bissau is one of the poorest countries in the world, but has a wealth of biodiversity. In this context, a particularly interesting case study is the Urok Maritime Community Protected Area, whose creation in 2005 involved the setting up of multi-scalar governance structures and mechanisms that have fostered participatory democracy. Many eyes are set on this experiment in the political ecology of conservation.